DNA Methylation Dynamics During the Differentiation of Retinal Progenitor Cells Into Retinal Neurons Reveal a Role for the DNA Demethylation Pathway - Dvoriantchikova, Galina; Seemungal, Rajeev J.; Ivanov, Dmitry (Frontiers in Molecular Neuroscience, 2019)
To evaluate the contribution of the DNA methylation and DNA demethylation pathways in retinal development, we studied DNA methylation in retinal progenitor cells (RPCs) and retinal neurons using a combination of whole genome bisulfite sequencing (WGBS) data obtained in our study and WGBS data collected from previous studies. The data was analyzed using Hidden Markov Model- and change point-based methods to identify methylome states in different segments of the studied genomes following genome annotation. We found that promoters of rod and cone phototransduction genes and rod photoreceptor genes, but not genes required for the development and function of other retinal phenotypes, were highly methylated in DNA isolated from human and murine fetal retinas (which mostly contain RPCs) and postnatal murine RPCs. While these highly methylated genomic regions were inherited by non-photoreceptor phenotypes during RPC differentiation, the methylation of these promoters was significantly reduced during RPC differentiation into photoreceptors and accompanied by increased expression of these genes. Our analysis of DNA methylation during embryogenesis revealed low methylation levels in genomic regions containing photoreceptor genes at the inner cell mass stage, but a sharp increase in methylation at the epiblast stage, which remained the same later on (except for DNA demethylation in photoreceptors). Thus, our data suggest that the DNA demethylation pathway is required for photoreceptor phenotypes in the developing retina. Meanwhile, the role of the DNA methylation and DNA demethylation pathways during RPC differentiation into non-photoreceptor retinal phenotypes might be less important.